PEMANFAATAN MINYAK KULIT BATANG GEMOR (Alseodaphne spp) SEBAGAI ALTERNATIF MAT REPELLENT ALAMI - Arhamsyah, Arhamsyah; Cahyana, Budi Tri (Kementerian Perindustrian, 2012)
The research about the utilization of gemor stem skin oil (Alseodaphne spp) as an alternative natural repellent mat has been done. This research aim to obtain essential oils from the bark using distillation and extraction method and used as repellent active ingredient. The result showed that the product is efficient and biodegradable proven by a test activity against the mosquito (Aedes aegypti). Varying the concentrations used are 10%, 20%, and 30% with the time observations to 02, 04, 06 and 08 hours after treatment. The results showed that anti-mosquito activity tends to increase with higer concentration. The use of 30% doses of Gemor bark essential oil is effective. The Effectiveness of the product against the mosquito (Aedes aegypti) and the economid value were compared with the innovator product containing DEET (N, N-diethyl-m-toluamid). Keywords: alseodaphne spp, repellent, concentration, Aedes aegypti, essential oils.